Conduction system pacing in adults with congenital heart disease - Matthew O'Connor (Elsevier, 2021)
Conduction system pacing is a growing sub-speciality within electrophysiology and its use is expanding. We conduct a review of the current state of knowledge, evidence and future direction for conduction system pacing in adult congenital heart disease.